2012
DOI: 10.1021/bm301109c
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Releasing Dendrimers as Antibacterial Agents

Abstract: The antibacterial activity of a series of nitric oxide (NO)-releasing poly(propylene imine) (PPI) dendrimers was evaluated against both Gram-positive and Gram-negative pathogenic bacteria, including methicillin-resistant Staphylococcus aureus. A direct comparison of the bactericidal efficacy between NO-releasing and control PPI dendrimers (i.e., non-NO-releasing) revealed both enhanced biocidal action of NO-releasing dendrimers and reduced toxicity against mammalian fibroblast cells. Antibacterial activity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 70 publications
(176 reference statements)
5
132
0
2
Order By: Relevance
“…For example, the NO-releasing MAP3 silica NPs showed approximately 30% viability 39 and NO-releasing dendrimer showed around 22% viability. 40 The lower toxicity of our NO/PPNPs than other NO-releasing NPs can be attributed to the relatively lower amount of NO per mg of NPs as mentioned above.…”
Section: Cytotoxicity Studymentioning
confidence: 79%
See 1 more Smart Citation
“…For example, the NO-releasing MAP3 silica NPs showed approximately 30% viability 39 and NO-releasing dendrimer showed around 22% viability. 40 The lower toxicity of our NO/PPNPs than other NO-releasing NPs can be attributed to the relatively lower amount of NO per mg of NPs as mentioned above.…”
Section: Cytotoxicity Studymentioning
confidence: 79%
“…39 Sun et al also reported a dendrimer NO-releasing system, which showed 3 logs killing against the Gram-positive S. aureus with a total NO release of 2.47 µmoles. 40 The possible mechanism by which the NO/PPNPs kill bacteria at such low NO concentrations is not fully understood. However, we hypothesized that the positive surface charge of NO/PPNPs (Table 1) facilitates the electrostatic binding of the NPs to the negatively charged bacterial surface, thereby increasing the antibacterial activity.…”
Section: Adhesion Of Nps To Bacteriamentioning
confidence: 99%
“…The NO-releasing dendrimers possessed superior bactericidal activity compared with silica, even though they released similar amounts of NO (t[NO] 2h ). Indeed, less NO was required to eradicate A. actinomycetemcomitans (1.5 vs. 3.2 µmol/mL for dendrimer and silica, respectively) and P. gingivalis (0.8 vs. 1.6 µmol/mL for dendrimer and silica, respectively) because of enhanced bacterial association of the dendritic scaffold (Sun et al, 2012). Despite storing and releasing more NO, similar concentrations of PROLI/NO were required to kill periodontopathogens, albeit at larger NO levels (3.1 and 25.2 µmol/mg for P. gingivalis and A. actinomycetemcomitans, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…long chain quaternary ammonium salts [141]. NO-releasing polypropylenimine dendrimers have been developed which allow higher levels of NO release per 'backbone' molecule over traditional NO donors [142]. NO releasing polymers and nanoparticles could be used either as coatings to prevent biofilm formation on surfaces such as catheters, prosthetic implants or contact lenses as well as industrial surfaces, or delivered in formulation either systemically or topically to treat biofilms on tissues.…”
Section: No Polymers and Nanoparticlesmentioning
confidence: 99%